Enhanced light extraction efficiency of GaN-based light-emittng diodes by nitrogen implanted current blocking layer. (October 2016) - Kim, Yong Deok; Oh, Seung Kyu; Park, Min Joo; Kwak, Joon Seop
Graphical abstract: Highlights: A nitrogen implanted current-blocking layer was successfully demonstrated. Light-extraction efficiency and radiant intensity was increased by more than 20%. Ion implantation was successfully implemented in GaN based light-emitting diodes. Abstract: GaN-based light emitting diodes (LEDs) with a nitrogen implanted current-blocking layer (CBL) were successfully demonstrated for improving the light extraction efficiency (LEE) and radiant intensity. The LEE and radiant intensity of the LEDs with a shallow implanted CBL with nitrogen was greatly increased by more than 20% compared to that of a conventional LED without the CBL due to an increase in the effective current path, which reduces light absorption at the thick p-pad electrode. Meanwhile, deep implanted CBL with a nitrogen resulted in deterioration of the LEE and radiant intensity because of formation of crystal damage, followed by absorption of the light generated at the multi-quantum well(MQW). These results clearly suggest that ion implantation method, which is widely applied in the fabrication of Si based devices, can be successfully implemented in the fabrication of GaN based LEDs by optimization of implanted depth.